2016
DOI: 10.1089/pho.2015.3922
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Sensitivity of Trichophyton and Aspergillus Conidia to Inactivation by Violet-Blue Light Exposure

Abstract: This version is available at https://strathprints.strath.ac.uk/54841/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The final 79 research articles reviewed contained inactivation data on clinically relevant and food‐associated microorganisms exposed to violet‐blue light between 380 and 480 nm. Data from each article were extracted, summarized and tabulated (see Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final 79 research articles reviewed contained inactivation data on clinically relevant and food‐associated microorganisms exposed to violet‐blue light between 380 and 480 nm. Data from each article were extracted, summarized and tabulated (see Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Haughton et al (2012) inactivated Campylobacter jejuni using 395 nm light, while Bumah et al (14,15) demonstrated the antimicrobial efficacy of 470 nm light against Salmonella enterica and S. aureus. Additionally, a small number of bacterial endospores, fungi and yeasts have been inactivated using violet-blue light (16)(17)(18)(19)(20)(21)(22)(23). To date, little is known about viral susceptibility; however, there is now published evidence demonstrating 405 nm light inactivation of a viral surrogate, bacteriophage ɸC31, and a mammalian virus, feline calicivirus, without the requirement of additional photosensitizers (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Moorhead et al used 405-nm aBL for inhibiting the growth of Trichophyton rubrum , Trichophyton mentagrophytes , and Aspergillus niger (Moorhead et al, 2016b). On agar plates, the growth of the microconidia of T. rubrum and T. mentagrophytes was completely inhibited after an exposure of 504 J/cm 2 aBL.…”
Section: Efficacy Of Antimicrobial Blue Light Inactivation Of Pathmentioning
confidence: 99%
“…Up to now the elimination of fungi by light treatment has been studied with single-photon excitation (see Wang et al, 2017 for a review). These studies made it possible to demonstrate the possibility of inhibiting growth or even inactivating certain fungi by light treatment without using exogenous photosensitizers (Murdoch et al, 2013 ; Moorhead et al, 2016 ; Guffey et al, 2017 ; Trzaska et al, 2017 ) and to identify certain endogenous photosensitizers such as porphyrins (Fraikin et al, 1996 ). However, little is known of the initiation site of oxidation, the intra-cellular dynamics of dispersion and the effect of power excitation modulation with two-photon excitation.…”
Section: Discussionmentioning
confidence: 99%